Effect of Competence and Career Development on Turnover and It’s Impact on Productivity - Umi Rusilowati, Hira Maulida (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2020)
The purpose of this study was to determine the effect of competency on turnover, to determine the effect of career development on turnover, to determine the effect of competencyand career developmentsimultaneously on turnover, to determine the effect of competence on productivity, to determine the effect of career development on productivity, to determine the effect of competencyand career developmentsimultaneously on productivity, to find the effect of turnover on productivity at PT. Reckitt Benckiser Indonesia. The method used in this study was the STATA version 14.2 program. The population was 319 employees and 177 respondents. The result of this study is competence has an effect on turnover, career development has an effect on turnover, competence and career development has an effect on turnover, competence has an effect on productivity, career development has an effect on productivity, competence and career development has an effect on productivity, turnover has an effect on productivity.